Study of the Removal of 4-Nitrophenol from Aqueous Media by Adsorption on Different Materials - Villarroel-Jorquera, M; Villarroel-Jorquera, M (Sociedad Chilena de Quimica, 2016)
The removal of 4-Nitrophenol (4-NP) from aqueous media by adsorption is studied in a batch system using different porous materials: activated carbon, zirconia, alumina, sepiolite, natural zeolite and 13X zeolite. Depending on their adsorption capacities, the best adsorbent was chosen to be impregnated with different levels of nickel (Ni) in order to study the adsorption by π-complexation in batch and continuous systems. The samples of Ni(x)/support (x= 2, 4, 6%) were prepared by wet impregnation and were characterised using the same method as with all the materials, by N2 adsorption-desorption using the BET method, surface acidity and Z potential measurements by electrophoretic migration. The samples were measured in a UV-Vis electrophotometer at a wavelength of 318 nm, while the adsorption capacity of the material in the batch system was determined by calculating the difference in concentration once the adsorbent became saturated after an initial concentration of ∼20 ppm, and in the continuous system this was done by integrating the area under the adsorption curve. The results suggest that adsorption capacity depends on the specific BET area, apparent acid strength and the IEP of each support, and that it varies with the addition of Ni. © 2016, Sociedad Chilena de Quimica. All rights reserved.